Straight after the turn: the role of the parietal lobes in egocentric space processing. - Seubert, J; Humphreys, G; Muller, H; Gramann, K (2008)
Spatial information processing with respect to an egocentric reference frame has been shown to recruit a fronto-parietal network along the dorsal stream. The present study investigates how brain lesions in the relevant areas affect the ability to navigate through computer-simulated tunnels shown from a first person perspective. Our results suggest that parietal, but not frontal, patients are impaired in this task. They confused the direction of tunnel turns more frequently and made less accurate judgments about the location of the end position. Errors in map drawing suggest that the impairment may be linked to deficits in updating cognitive heading in the absence of corresponding perceptual information from the virtual environment.